The Construction of Cultural Gene Map and Revitalization Strategies for Industrial Heritage: A Case Study of Hanyang Ironworks in Wuhan - Li, Qiguo; Hu, Yingfeng (MAJ - Malaysia Architectural Journal, 2025)
Industrial heritage serves as a powerful testament to the development of urban civilization, inheriting and continuing the urban cultural context. Currently, urban construction in China has entered a phase focused on enhancing the quality of existing assets. As an important stock resource in urban development, the protection and reuse of industrial heritage have become a hot topic of research in recent years, with the focus gradually shifting from singular ’material preservation’ to diverse ’cultural output.’ Studies have shown that during the transformation of industrial heritage, a lack of clear understanding of its cultural system often leads to phenomena such as ’homogenization,’ ’fragmentation,’ and ’blind modification.’ Furthermore, due to insufficient exploration of the cultural value of industrial heritage, there can be misinterpretations when conveying its cultural significance, causing people to view industrial heritage as low-quality culture. This cultural conflict hampers the protection and reuse of industrial heritage. Therefore, preserving, developing, and passing on the cultural aspects of industrial heritage is the main focus of this study. Using Hanyang Ironworks in Wuhan, Hubei Province, as a case study, this research introduces the concept of cultural genes from the perspective of biological genetics. First, it integrates grounded theory with the landscape gene extraction method to establish a process for extracting cultural genes from industrial heritage. Next, based on typology principles and the ’N-Level Coding’ theory, an industrial heritage cultural gene map is created. Finally, the cultural genes in the map are organized and summarized according to three types of genes: primary genes, attached genes, and mixed genes. Through an analysis of the inheritance patterns of different cultural genes, the study proposes strategies for revitalizing the cultural genes of industrial heritage.